Evaluation of spatial-structural properties and thermal technical indicators of autoclave-free aerated concrete produced from industrial waste (Международный научный журнал «Инженер», 2026)
This article explores the phase-structural properties and thermal specifications of autoclaved gazobetonsamples using industrial waste, including quartz sand and steel smelting slag. The size, shape, and distributionof pores in Gazobeton have been estimated using electron microscopy and radiofascial analysis methods.Based on the results of the experiment conducted, the thermal conductivity coefficient was determined in therange 0.138–0.147 W/(m·°C) in gazobeton samples enriched with industrial waste. The results of the studyshowed that the optimal size and distribution of pores significantly improves the thermal insulating andmechanical properties of the material. The microstructure and analysis of the mineral phase composition ofgazobeton determined its potential to increase energy efficiency and strength indicators.